Revitalising The Regulation of Zakat Institutions in Indonesia to Achieve Economic Justice - Mulyono Jamal; Agung Lia Handayani; Ainun Amalia Zuhroh (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2023)
This research aims to provide a solution to the dual function problem of BAZNAS. The problem required the regulatory aspect improvement. Indentifiying national business governance issues, improving the regulation of Law No. 23/2011 on zakat management is crucial. The separation of the two functions of BAZNAS will also reduce the risk of misuse of zakat funds which can be significantly reduced, an independent regulator can conduct monitoring and auditing more effectively. This research uses qualitative method or conceptual review of secondary data through literature study approach. The purpose of the research is to help identify, analyze, and overcome problems and challenges faced in society. The results of the study to achieve economic justice through zakat, the BAZNAS institution needs to separate its function as implementer. To achieve economic justice through zakat, BAZNAS needs to separate its functions as implementer. This separation of functions for BAZNAS will also reduce the risk of misuse of zakat funds which can be reduced significantly. Meanwhile, regulations regarding zakat can be more optimally carried out by the Ministry of Religion independently in monitoring and auditing more effectively, thereby reducing the potential for abuse by implementers.